Xanthelasma palpebrarum with arcus cornea: A clinical and biochemical study - Pragya Ashok Nair; Chaitali R Patel; Jaishree D Ganjiwale; Nilofar Gulamsha Diwan; Nidhi Bhimjibhai Jivani (Indian Journal of Dermatology, 2016)
Background: Xanthelasma palpebrarum (XP) is characterized by sharply demarcated yellowish flat plaques on upper and lower eyelids. It is commonly seen in women with a peak incidence at 30–50 years. It is also considered as the cutaneous marker of underlying atherosclerosis along with the disturbed lipid metabolism. XP and corneal arcus are associated with increased levels of serum cholesterol and low-density lipoprotein (LDL) cholesterol. Aims and Objectives: To study the clinical pattern of XP, its relationship with lipid profile and association with arcus cornea. Materials and Methods: This study was conducted at Department of Dermatology and Opthalmology, between August 2013 and January 2015. Patients with clinical diagnosis of XP who visited skin outpatient department and willing to undergo lipid profile test and eye examination were included in the study. Data regarding demographics, clinical findings, family history, and past history were noted along with the lipid profile details. Data of age-matched healthy controls were taken for comparison. The clinical profile of the participants was presented using frequency and proportions. Gender wise analysis comparing the lipid profile in cases with XP and without XP was done using independent sample t-test. Results: Total 49 patients of XP, 81.6% were females. Maximum, 35% patients were among 50–60 years of age and 69.4% were homemakers by occupation. The average lipid values were-cholesterol 210.57 mg%, triglyceride 123.06 mg%. LDL 142.79 mg% and VLDL 30.95 mg% among patients of XP. Arcus cornea was found in 20% cases of XP. Conclusions: Patients of XP requires proper investigation at the onset and regular follow-up thereafter for any altered lipid profile and early diagnosis of coronary artery disease.